آليات التشكيل الحجاجي في ديوان الزمن الأخضر لأبي القاسم سعد الله - غريب, فتح الله, آسيا نريمان; بالنور, فاطمة (Univercty of Eloued, 2020)
In this study we dealt with the following subject "The mechanisms of argumentative formation in the green book era" of " Abu Al Quassim Saad Allah" . We analyzed the samples of rhetorical, linguistic and semi-logical mechanisms mentioned in book . We also highlighted its role in persuading and influencing the receiver. Therefore, it was considered as a historical record of its experiences and positions during an Important era in Algeria's history. Through this analysis, we concluded that these mechanisms are a strong support for confirming its ideas and conveying them to the mind and heart of the receiver, especially the rhetorical mechanisms that embodied and portrayed that era with its tragedy and pain. It also built a persuasive and influential speech that achieved the goals of " Abu Al QuassimSaad Allah " through a poetic discourse charged with an argumentative force derived from various arguments. Thus, he achieved a conjugation between rhetoric and argumentation.
Keywords: التشكيل - الحجاجي